Genetics of vascular malformation and therapeutic implications. Issue 4 (August 2019) - Zúñiga-Castillo, Miguel; Teng, Christopher L.; Teng, Joyce M.C.
Abstract : Purpose of review: Vascular malformations (VaMs) are a consequence of disrupted morphogenesis that may involve arterial, capillary, venous, or lymphatic endothelium alone or in a combination. VaMs can have serious health impacts, leading to life-threatening conditions sometimes. Genetic mutations affecting proliferation, migration, adhesion, differentiation, and survival of endothelial cells, as well as integrity of extracellular matrix are believed to be the pathogenesis of these disorders. Here, we present an updated review of genetic mutations and potential therapeutic targets for VaMs. Recent findings: Increased number of genetic mutations have been discovered in vascular anomalies via targeted deep sequencing. When a genetic defect is identified, it often presents in only a small percentage of cells within the malformation. In addition, mutations within the same gene may result in different clinical phenotypes. Management of VaMs can be challenging depending on the severity and functional impairment associated. There are no standard treatment algorithms available to date for VaMs, therefore the disorder has significant unmet clinical needs. Currently, the focus of therapeutic development is to target constitutively activated intracellular signaling pathways resulted from genetic mutations. Summary: Knowledge about the genetic mutations and altered signaling pathways related to VaMs have improved our understanding about the pathogenesis of vascular anomalies and provided insights to the development of new targeted therapies.